Consumption of scrap foods and food attitudes of higher level students. University - Ruiz-Aquino , Mely (2018)
Objective: To determine the relationship between the consumption of junk foods and the alimentary attitudes in the students of the University of Huánuco; in 2014. Methods: the study was observational, analytical and cross-sectional; with correlational design. The population consisted of 1342 university students of Health Sciences; whose sample was selected probabilistically and stratified were 298 students to whom it was applied: an interview, a questionnaire of junk food consumption and a scale of food attitudes; previously validated and reliable. The ethical considerations of the investigation were applied. Descriptive and inferential analysis was carried out using the Rho correlation coefficient of Spearman, after normality of kolmogorov-Smirnov, supported by the SPSS V19. Results: 79, 3% (237) of the sample, indicated consuming junk foods. 75.6% (226) expressed positive food attitudes. The overall correlation was analyzed between the variables: junk food consumption and food attitudes, obtaining a significant low level correspondence (Rho = 0, 174 and p = 0.003); also, with the same tendency, between the consumption of junk foods and diet as a dimension of dietary attitudes (Rho = 0.195), this being significant (p = 0.001). There was no correlation between the consumption of junk foods and the dimension traits of bulimia- concern for food and oral control as part of the food attitudes. Conclusions: There is a low significant relationship between the consumption of junk foods and the nutritional attitudes of university students, which is why healthy eating policies must be implemented.